Inflation expectation uncertainty in a New Keynesian framework - Angela Fuest; Torsten Schmidt (RWI - Leibniz-Institut für Wirtschaftsforschung, 2020)
For monetary policy guiding inflation expectations provides an instrument to achieve price stability. However, expectation uncertainty may undermine monetary policy's ability to stabilise the economy. This study examines the effects of inflation expectation uncertainty on inflation, inflation expectations and the output gap by means of a structural VAR with stochastic volatility in mean. Inflation expectation uncertainty negatively affects the inflation rate and the output gap, without having a distinct effect on the level of expectations. This result is replicable with a model in which uncertainty is approximated by a cross-sectional survey measure. Furthermore, simulating an uncertainty shock in a DSGE model shows that the demand channel dominates the supply channel of an inflation expectation uncertainty shock. – – Die Steuerung der Inflationserwartungen ist ein geldpolitisches Instrument zur Erreichung von Preisstabilität. Allerdings kann Erwartungsunsicherheit die Fähigkeit der Geldpolitik zur Stabilisierung der Wirtschaft untergraben. In dieser Studie werden die Auswirkungen der Unsicherheit der Inflationserwartungen auf die Inflation, die Inflationserwartungen und die Produktionslücke mit Hilfe eines strukturellen VAR mit stochastischer Volatilität untersucht. Es zeigt sich, dass sich Unsicherheit der Inflationserwartungen negativ auf die Inflationsrate und die Produktionslücke auswirkt, ohne einen deutlichen Effekt auf das Niveau der Erwartungen zu haben. Dieses Ergebnis ist mit einem Modell reproduzierbar, bei dem die Unsicherheit durch ein Querschnittserhebungsmaß approximiert wird. Darüber hinaus zeigt die Simulation eines Unsicherheitsschocks in einem DSGE-Modell, dass der Nachfragekanal den Angebotskanal eines Unsicherheitsschocks der Inflationserwartung dominiert.
Keywords: E31; E52; C32; C63; 330; uncertainty; inflation expectations; Phillips curve; New Keynesian model